Pengaruh Pelatihan, Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan PT Osi Electronics Batam - Fitriani Lubis; David Humala Sitorus (eCo-Buss, 2024)
The objectives of this study are to identify and evaluate the impact of training on employee performance at PT OSI Electronics Batam, to identify and evaluate the impact of work motivation on performance, and to identify and evaluate the impact of training and work discipline on employee performance. In this study, an associative technique was applied. 228 employees of PT OSI Electronics Batam made up the study's population, and 145 were chosen as the study's sample from the total using the Slovin formula. In this study, questionnaires, document analyses, and interview approaches were employed to collect data (questionnaires). The Classical Assumption Test, Multiple Linear Regression, t test, f test, and coefficient of determination are data analysis methods used in research. processing data. The SPSS program was utilized in this study's data processing (version 25). According to the study's findings, training, work motivation, and work discipline individually or in combination positively affect employees at PT OSI Electronics Batam